Enantioselective Synthesis of d‐ and l‐α‐Amino Acids by Enzymatic Transamination Using Glutamine as Smart Amine Donor. Issue 4 (20th December 2018) - Heuson, Egon; Charmantray, Franck; Petit, Jean‐Louis; de Berardinis, Véronique; Gefflaut, Thierry
Abstract: Enzymatic transamination is a useful method for the green and highly enantioselective synthesis of chiral amines and non‐canonical amino acids which are of major importance as intermediates in medicinal chemistry. However, transamination reactions are usually reversible and synthetic applications of transaminases often require the implementation of an equilibrium shift strategy. Herein, we report a highly effective approach using glutamine as smart amine donor. This amino acid is converted upon transamination into 2‐oxoglutaramate which undergoes a fast cyclisation displacing the transamination equilibrium. We have developed a new activity assay in order to identify transaminases from biodiversity able to convert various α‐keto acids into valuable amino acids ofl ‐ ord ‐series in the presence of glutamine as amine donor. Discovered transaminases were then used to prepare in high yield and with high enantioselectivity three amino acids of pharmaceutical importance, homophenylalanine, homoalanine and tert ‐leucine by simply using a nearly stoichiometric amount of glutamine as amine donor. Abstract :